A Comparison Study of Choledocholithotomy with T-tube Drainage and Choledochoduodenostomy for Surgically Managing Choledocholithiasis - Santanu Sarma; Nirmal Agarwal; Biswajit Das (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2024)
Background and aim: Though recent trends in the management of choledocholithiasis shifted to endoscopic retrograde cholangiopancreatography (ERCP) and Laparoscopy, the traditional methods of choledochotomy and T-tube drainage and choledochoduodenostomy (CDD) are still relevant. Residual or missed stones and cholangitis are the problems faced by surgeons following biliary surgery for CBD stones. We aim to compare the outcome of the two traditional methods. Material and Methods: In this retrospective study, 47 patients with choledocholithiasis were included, out of which 19 patients whose CBD was dilated more than 12mm choledochoduodenostomy was performed, and in the remaining 28 patients, choledocholithotomy and T-tube drainage were performed, and their outcomes reviewed. Intra-operative findings, including any difficulty encountered and postoperative findings like any complications, duration of total hospital stay, and incidence of retained stones, were recorded. Results: The patients with post-cholecystectomy status encountered considerable adhesions. The wound infection rate was 14.3% in the T-tube group and 10.5% in the CDD group. One patient with CDD had 400ml of bile in the drain, which subsided spontaneously. Another with T-tube drainage had a collection of around 300ml of bile following T-tube removal. Hospital stay in the T-tube drainage group was longer. In two cases of the T-tube group, there were retained stones, whereas in the CDD group, there were none. Conclusions: Open surgical procedures for choledocholithiasis still have an important role to play. Both techniques are easy and safe to perform. Choledochoduodenostomy lowers the chances of retained and recurrent stones.